Childhood malnutrition in households with contemporary siblings: a scenario from urban Bangladesh - Das, Jui; Kumar Das, Sumon; Hasan, T; Syed Golam Faruque, Abu; Ahmed, Salma; Ferdous, Farzana; Begum, R; Jobayer Chisti, Mohammod; Malek, M A; Mamun, Abdullah (© 2015 Nature Publishing Group, 2016)
This article was published in European Journal of Clinical Nutrition [© 2015 Nature Publishing Group] and the definite version is available at: https://www.ncbi.nlm.nih.gov/pubmed/25969397